RATIO OF CALCIUM CARBONAT WITH CADMIUM AND COPPER IN ALGAE HALIMEDA SP FROM DIFFERENT POLLUTED ENVIRONMENT - Muhammad Farid Samawi Farid; Hendra Hasim; Nenni Asriani; Isyanita Isyanita (Jurnal Ilmu Kelautan SPERMONDE, 2022)
Accumulated Cd, and Cu in the algae Halimeda sp at various levels of metal pollution has been done on the islands Laelae, Baranglompo and Karanrang. The aims of research to know accumulation Cd, Cu and their ratio with CaCO3 in algae Halimeda sp at different level water pollution in Spermonde Archipelago. Sample algae Halimeda sp was collected in three location with different level of metal pollution within Spermonde Archipelago, namely Laelae, Barranglompo and Karanrang Islands. The highest concentrations Cd and Cu are found on the island Laelae, followed Baranglompo and Karanrang, showing anthropogenic influence on the level of metal in the algae Halimeda sp. There are differences in the pattern of ratio Cd/Ca and Cu/Ca among samples of algae Halimeda sp due to the influence of external input. Algae Halimeda sp sensitive to the accumulation of heavy metals Cd and Cu. These results prove that the algae Halimeda sp can be used as indicators of heavy metals pollution of Cd and Cu in marine waters